OPTIMIZING SELF-MANAGEMENT FOR PREVENTION AND CONTROL OF DIABETES MELLITUS THROUGH SELF-MONITORING PRACTICES AND THE DIARY DM APPLICATION - Handayani, Nur Septia; Retrialisca, Fitri; Purwanti, Endah; Qomari, Yusuf Maulana; Ferrari, Rifky Mahdiyah; Wijianto, Buyung; Keyesa, Talidah Nur; Zaen, Maulana Biagi (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Diabetes mellitus self-management activities, according to the Association of Diabetes Care & Education Specialists, involve monitoring blood glucose and decreasing risk factors. These two activities can be supported by using the Diary DM application, which helps to record blood glucose levels and determine nutritional status to support the reduction of risk factors. The aim of this community service is to optimize self-management for the prevention and control of diabetes mellitus through self-monitoring practices and the Diary DM application. The methods of this community service include socializing, demonstrating, and direct practice on how to conduct blood glucose self-checks and utilize the Diary DM application. The total number of participants in this community service is 20, with an average productive age of 53.6 years. The results of the pre-test and post-test analysis showed an increase in participants' knowledge regarding DM self-examination, with an initial score of 63.88 (pre-test) rising to 86.25 (post-test). Positive attitudes were observed, reflecting participants' awareness and willingness to conduct blood glucose self-checks at home and implement the use of the Diary DM application. The majority of the community service's evaluations indicated "good" and "very good" ratings regarding the speakers, the topics, and the implementation of community service aspects.